Aspects of psychopathic personality relate to lower subjective and objective professional success. (February 2022) - Eisenbarth, Hedwig; Hart, Claire M.; Zubielevitch, Elena; Keilor, Tristan; Wilson, Marc; Bulbulia, Joseph; Sibley, Chris G.; Sedikides, Constantine
Abstract: Which aspects of psychopathic personality, if any, contribute to professional success? Previous research suggests that fearless dominance does so. Yet, it also suggests that self-centered impulsivity impairs professional success. Here, we address this differential pattern in a preregistered, multi-wave study involving a large, nationally representative sample ( N = 2969 New Zealanders). We test the (a) replicability of prior findings using a new objective measure of professional success, and (b) stability of our findings across two annual assessments from 2011 and 2012. Fearless dominance is positively associated, but self-centered impulsivity is negatively associated, with subjective professional success. Controlling for age, gender, education level, and time in the current job does not alter these associations. Further, self-centered impulsivity and coldheartedness are negatively related with objective professional success. However, only the effect of coldheartedness remains after considering demographic variables. These relations hold for predicting subjective and objective professional success one year later. Together, aspects of psychopathic personality are linked negatively to objective professional success, a finding that challenges popular beliefs about the functional benefits of psychopathy in the workplace.